Cannabinoid Discrimination and Antagonism by CB(1) Neutral and Inverse Agonist Antagonists - Kangas, Brian D. (The American Society for Pharmacology and Experimental Therapeutics, 2013)
Cannabinoid receptor 1 (CB(1)) inverse agonists (e.g., rimonabant) have been reported to produce adverse effects including nausea, emesis, and anhedonia that limit their clinical applications. Recent laboratory studies suggest that the effects of CB(1) neutral antagonists differ from those of such inverse agonists, raising the possibility of improved clinical utility. However, little is known regarding the antagonist properties of neutral antagonists. In the present studies, the CB(1) inverse agonist SR141716A (rimonabant) and the CB(1) neutral antagonist AM4113 were compared for their ability to modify CB(1) receptor–mediated discriminative stimulus effects in nonhuman primates trained to discriminate the novel CB(1) full agonist AM4054. Results indicate that AM4054 serves as an effective CB(1) discriminative stimulus, with an onset and time course of action comparable with that of the CB(1) agonist Δ(9)-tetrahydrocannabinol, and that the inverse agonist rimonabant and the neutral antagonist AM4113 produce dose-related rightward shifts in the AM4054 dose-effect curve, indicating that both drugs surmountably antagonize the discriminative stimulus effects of AM4054. Schild analyses further show that rimonabant and AM4113 produce highly similar antagonist effects, as evident in comparable pA(2) values (6.9). Taken together with previous studies, the present data suggest that the improved safety profile suggested for CB(1) neutral antagonists over inverse agonists is not accompanied by a loss of antagonist action at CB(1) receptors.